Pelatihan Penyusunan Laporan Auditan oleh Kantor Akuntan Publik (KAP) Sarastanto dan Rekan bagi Mahasiswa STIE Semarang - Ratna Herawati; Agung Prajanto; Dian Indriana Hapsari (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
The rapid technological developments of this decade have had a positive impact on the transparency of information in financial reports. Transparent financial report information demonstrates the quality of the financial reports. Public accountants are tasked with providing an opinion on the fairness of the presented financial reports. The standard used by a public accountant in assessing the fairness of financial reports is the Public Accounting Auditing Standards (SPAP). The SPAP contains guidelines for carrying out the audit cycle systematically and in accordance with procedures, starting from the pre-engagement, planning, and reporting stages. Therefore, it is crucial to conduct audit report preparation training for prospective auditors, conducted by a team of lecturers from the Faculty of Economics and Business, Dian Nuswantoro University through a community service program. This community service activity took as participants prospective auditors from STIE Semarang students at KAP Sarastanto and Rekan in Semarang City. This activity was carried out so that prospective auditors could be provided with the knowledge and skills to complete the audit cycle from pre-engagement to reporting. The methods used in this community service program were presentations and mentoring, while the training material for preparing audit reports was carried out by the community service team and practitioners (auditors) from KAP Sarastanto and Rekan. The results of this training show that prospective auditors (STIE Semarang students) are able to understand the audit cycle systematically and are able to realize the importance of audit reports for stakeholders.